Indeks Zakat Nasional (IZN) sebagai Basis Indeks Kelembagaan Zakat di Baznas Provinsi D.I. Yogyakarta - Purnama, Lili; Abidin, Maulana; Ibi Satibi (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2023)
Indonesia is a country with the largest Muslim population in the world. So that the zakat instrument is believed to be a solution to reduce poverty and create prosperity. This study aims to analyze and determine the National Zakat Index (IZN) as the basis for the institutional index of zakat in BAZNAS Province, D.I. Yogyakarta. The method used is a quantitative literature analysis study with descriptive analysis techniques. The results of the study illustrate the value of the D.I. BAZNAS IZN. Yogyakarta in 2021 is 0.67, which comes from the components of the macro and micro dimensions. Then, zakat has an impact on reducing poverty when viewed from the poverty line, it has kifayah and nisab zakat